HISTORY OF RELIGIONS IN STRUCTURE OF HUMANITIES - Горбаченко, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the context of civilizational approach examined the history of religions and its place in the structure humanities that serves as a kind of spiritual formation as a value-semantic development and reproduction of human existence. History of Religions is a separate science, which includes new scientific knowledge, and, simultaneously, educational dystsplinoyu liberal education, whose main goal – to give the younger generation the amount and depth of knowledge about religion, in the form and scope that would allow it to form an adequate image Religion and objective attitude to it.